WAYS OF SOCIAL-ECONOMIC DEVELOPMENT OF REGIONS THROUGH INCREASING THE INVESTMENT CAPACITY (Marketing Journal, 2025)
The article analyzes the issues of ensuring the socio -economic development of the regions of Uzbekistan through the enhancement of their investment potential. It examines the structural components of the investment environment, practical directions of inve stment policy, and provides proposals and recommendations based on international experience and national practice. In addition, the article analyzes investment activity across regions and highlights the importance of infrastructure development, human capit al improvement, and the implementation of innovations.
Keywords: investment; investment potential; regional development; foreign investment; economic policy; innovation; infrastructure